Konsep Pendidikan Anak Usia Dini Perspektif Ibnu Sina - Nurul Qomariah Nurul (Sekolah Tinggi Ilmu Tarbiyah Muhammdiyah Muhammadiyah Bojonegoro, 2025)
This research is motivated by the fact that the world of education today can be seen that the national education system in Indonesia uses theories from Western education, one of which is in Early Childhood Education (PAUD) institutions so that the end result of the world of education causes children to have a Western mentality too. Meanwhile, the education of Islamic scientists is often ignored and they do not even know the difference between Western educational theory and the educational theory of Islamic scientists. In fact, in the world of education, there are many Muslim scientists whose ideas can still be used today, one of whom is Ibnu Sina. The aim of this research is to determine the concept and objectives of early childhood education from Ibn Sina's perspective. This type of research is library research. The data collection technique used by researchers is documentation techniques. Next, the data obtained is then analyzed using the content analysis method, which is a research method that involves a more in-depth discussion of the content of information, both written and printed in the mass media. The result of this research is that the concept of early childhood education taught by Ibn Sina is related to educational psychology. Children's education is related to the child's age level, talents and desires by knowing the background level of development. And the aim of early childhood education according to Ibnu Sina is that education must be directed at developing all the potential that students have so that they can develop perfectly, namely intellectual, physical and character development.